Quantum Mechanical Investigations of Copper(I)-Catalyzed Cycloaddition Reaction between Benzel Azide and Aryl Acetylene - الباني, نبيل (Latakia University Journal -Basic Sciences Series, 2020)
The mechanism of copper (I) catalyzed benzel azide - aryl acetylene cycloaddition (CuAAC) have been studied for systematic understanding of this relevant organic transformation, using DFT Methods: B3LYP, wB97XD, LC-wPBE and M06-2X with basis set 6-31G(d). The effect of the presence of solvents on the calculation results in the gas state was also studied. Theoretical results generally indicate that the reaction begins with the formation of the reactive compound (RC), and then the intermediate compound (IC) is formed via an initial transitional state, then the final product is formed starting from the IC via a second transitional state. Computational results are shown that the activation energy for benzel azide - aryl acetylene cycloaddition is lower than for methyl azide - methyl acetylene cycloaddition.The presence of the solvents slightly affects the Gibbs free energy of the transition states leading to the formation of the intermediate compound (IC),